Production of Greenhouse Tomatoes - Florida Greenhouse Vegetable Production Handbook, Vol 3 - George Hochmuth; Robert Hochmuth (EDIS)
The tomato is a very popular crop for production in greenhouses. Tomatoes are relatively easy to grow compared to cucumbers and lettuce, and yields can be very high. Demand for tomatoes is usually strong because of the vine-ripe nature and general overall high level of eating quality.